Pyroglutamate-Modified Amyloid Beta Peptides: Emerging Targets for Alzheimer´s Disease Immunotherapy - Perez-Garmendia, Roxanna; Gevorkian, Goar (Current Neuropharmacology, 2013)
Extracellular and intraneuronal accumulation of amyloid-beta (Aβ) peptide aggregates in the brain has been hypothesized to play an important role in the neuropathology of Alzheimer’s Disease (AD). The main Aβ variants detected in the human brain are Aβ1-40 and Aβ1-42, however a significant proportion of AD brain Aβ consists also of Nterminal truncated species. Pyroglutamate-modified Aβ peptides have been demonstrated to be the predominant components among all N-terminal truncated Aβ species in AD brains and represent highly desirable and abundant therapeutic targets. The current review describes the properties and localization of two pyroglutamate-modified Aβ peptides, AβN3(pE) and AβN11(pE), in the brain. The role of glutaminyl cyclase (QC) in the formation of these peptides is also addressed. In addition, two potential therapeutic strategies, the inhibition of QC and immunotherapy approaches, and clinical trials aimed to target these important pathological Aβ species are reviewed.
Keywords: pyroglutamate-modified amyloid-beta